Proximate and Macro Minerals Content of Gastropods in the Waters of Teluk Cina Lemukutan Island West Kalimantan - Warsidah Warsidah; Mega Sari Juane Sofiana; Apriansyah Apriansyah; Lucky Hartanti; Desriani Lestari; Ikha Safitri; Shifa Helena (Jurnal Biologi Tropis, 2022)
Lemukutan Island in West Kalimantan has marine natural resources with a high level of diversity such as seagrass, coral reefs, macroalgae, and gastropods. Gastropods are one of the largest Mollusc phylum groups that are abundant in the waters of Lemukutan Island. Several types of gastropods have been reported to have high economic value and high nutritional content as well as macro minerals such as Na, Ca, K, F, and P. Therefore, these biota are more widely used as food. This study aims to analyze the proximate and mineral content of gastropods (Lambis and Monetaria) from the waters of Lemukutan Island. The moisture content and ash content of the sample were determined by the gravimetric method. The results of the study found that macro mineral content was determined in Lambis and Monetaria by Atomic Absorption Spectrophotometer (AAS). The protein content in both types of gastropods is quite high. Monetaria has a higher protein content (63.69%) than Lambis (50.06%). However, the fat content in Lambis is 1.88% and Monetaria is 1.14%. The highest mineral content of these two types of gastropods is iron (Fe). Lambis and Monetaria have Fe content of 0.2762 mg/kg and 0.1818 mg/kg, respectively.